On the wings of time : Rome, the Incas, Spain, and Peru - MacCormack, Sabine (Princeton University Press, 2007)
Historians have long recognized that the classical heritage of ancient Rome contributed to the development of a vibrant society in Spanish South America, but was the impact a one-way street? Although the Spanish destruction of the Incan empire changed the Andes forever, the civil society that did emerge was not the result of Andeans and Creoles passively absorbing the wisdom of ancient Rome. Rather, Sabine MacCormack proposes that civil society was born of the intellectual endeavors that commenced with the invasion itself, as the invaders sought to understand an array of cultures. Looking at the sixteenth- and seventeenth-century people who wrote about the Andean region that became Peru, MacCormack reveals how the lens of Rome had a profound influence on Spanish understanding of the Incan empire.--Publisher description.